Anaerobic Digestion of Food Waste Enhanced by Rubber Sludge Biochar - Muhammad, Khadijah; Azmi, Auni Nasuha; Yahya, Noor Yahida (International Journal of Integrated Engineering, 2025)
Food waste (FW) is a huge global issue and predominantly occurs in highly urbanized and developed countries. Anaerobic digestion (AD) is recognized as one of the most sustainable, cost-effective and efficient means to cater to the problem. Despite that, AD process often suffers from system over-acidification, high lag time, high carbon dioxide content, low methane yield and prone to system failure. This study characterized the properties and evaluated the effects of rubber sludge-derived biochar addition on anaerobic digestion of food waste (ADFW) as well as explored the optimum conditions of ADFW to have an enhanced biogas production. Rubber sludge-derived biochar was fabricated under pyrolytic temperature of 500°C. ADFW pH range used for this research work were 4-8. Further, investigation focused on the biochar dosage of 5, 10, 15, 20 and 25 g with the duration of 7 to 35 days. The findings of this study indicate maximum biogas generated at pH 6 with 15 g BC/L FW of biochar dosage for 35 days.